Metode Pendidikan Dalam Keluarga - Rohayu Fadilla; Dwi Nomi Pura; Dahlia Dahlia; Zakia Jumatul Aini; Anggi Regia Anandari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Education within the family is the primary foundation for character building and early childhood development. Parents play a crucial role in instilling moral values, religion, discipline, and positive habits in children. This article discusses family education methods based on the results of an interview with a housewife who has two elementary school-aged children. The study was conducted using a semi-structured interview method. The results of the interview show that the educational methods used include setting an example, giving advice, enforcing discipline, and habituating positive activities. Parents also adapt their parenting style to the unique character of each child. The main obstacle in educating children at home is the excessive use of gadgets, which affects the children's learning focus. To overcome this issue, parents limit gadget use and redirect their children to more beneficial activities, such as playing with friends and reciting the Quran.